The Irish model of religious education in primary school: the search for tolerance - Надирова, Г. Е. (Journal of Oriental Studies, 2018)
This article examines the Irish educational system at the primary school level, its constitutional foundations, legislation, with emphasis on how it potentially and in fact affects the religious freedom of children from Muslim families. The work fits into the framework of the scientific project 3260 / GF4 «Religious education in a changing world: an innovative Kazakhstan and a thinking nation», one of whose tasks is to study foreign experience in building a system of religious education. The article is based on the results of a study of sources and a number of documents concerning religious education in Ireland and the problem of the tolerance of Irish society to other religions. In most cities in Ireland there are only one or two national schools, and they are usually denominational in nature, mostly Catholic, and act according to an integrated curriculum. This leads to problems of freedom of conscience, when representatives of religious minorities, including Muslims, or those who do not practice religious faith, are forced to attend a confessional school in their district. In such situations, it is recommended that the legal doctrine of «reasonable accomodation» be used as a basis for decisions on which religious practices in the classroom should be harmonized, and not represent unjustified difficulties for other students, teachers or for the school system as a whole. The article gives an idea of the degree of democracy and the existence of certain restrictions in the school system of one of the European countries and a material for comparing situations «here and there.»